2018
DOI: 10.2109/jcersj2.17231
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compatibility of Sr<sub>2</sub>MgMoO<sub>6−δ</sub> with representative electrolyte materials and interlayer materials for solid oxide fuel cells

Abstract: Sr 2 MgMoO 6¹¤ (SMM) is one of promising anode materials for direct internal reforming solid oxide fuel cells as its excellent performance has been demonstrated. However, it is necessary to be chemically compatible with the electrolyte material to realize the original performance. In this study, we investigate chemical compatibility between SMM and typical electrolyte materials (8% mol Y 2 O 3 92% mol ZrO 2 ; YSZ, 10% mol Sc 2 O 3 1% mol CeO 2 89% mol ZrO 2 ; ScSZ, La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3¹¤ ; LSGM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Good chemical compatibility between LSGM and anodes with a double perovskite structure was shown for: La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3−δ and Sr 2 TiMoO 6−δ after calcining the samples at 1000 • C for 10 h in an atmosphere of 5% H 2 /Ar [160], La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3−δ and Sr 2 Fe 1.5 Mo 0.5 O 6−δ after heat treatment at 1200 • C for 24 h in air [161], La 0.88 Sr 0.12 Ga 0.82 Mg 0.18 O 3−δ with Sr 2 NiMoO 6−δ at 1000 • C for 20 h [162,163] and Sr 2 Ni 0.75 Mg 0.25 MoO 6−δ at 1100 • C for 20 h [164] and at 1250 • C for 2 h [163]. The formation of secondary phases between LSGM and double perovskite anodes was observed for La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3−δ and Sr 2 MgMoO 6−δ after calcining at 1100 • C [165], for La 0.88 Sr 0.12 Ga 0.82 Mg 0.18 O 3−δ and Sr 2 ZnMoO 6 at 1000 • C for 20 h [166] and for La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3−δ at 1300 • C for 10 h with Sr 2 Ni 0.7 Mg 0.3 MoO 6−δ [167] and, after heat treatment at 1200 • C for 24 h, with Sr 2 CoMoO 6−δ [161], Sr 2 NiMoO 6−δ [161] and Sr 2 MgMoO 6−δ [168].…”
Section: Sample Samples Obtaining Method; Annealing Temperature (°C) ...mentioning
confidence: 88%
See 1 more Smart Citation
“…Good chemical compatibility between LSGM and anodes with a double perovskite structure was shown for: La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3−δ and Sr 2 TiMoO 6−δ after calcining the samples at 1000 • C for 10 h in an atmosphere of 5% H 2 /Ar [160], La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3−δ and Sr 2 Fe 1.5 Mo 0.5 O 6−δ after heat treatment at 1200 • C for 24 h in air [161], La 0.88 Sr 0.12 Ga 0.82 Mg 0.18 O 3−δ with Sr 2 NiMoO 6−δ at 1000 • C for 20 h [162,163] and Sr 2 Ni 0.75 Mg 0.25 MoO 6−δ at 1100 • C for 20 h [164] and at 1250 • C for 2 h [163]. The formation of secondary phases between LSGM and double perovskite anodes was observed for La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3−δ and Sr 2 MgMoO 6−δ after calcining at 1100 • C [165], for La 0.88 Sr 0.12 Ga 0.82 Mg 0.18 O 3−δ and Sr 2 ZnMoO 6 at 1000 • C for 20 h [166] and for La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3−δ at 1300 • C for 10 h with Sr 2 Ni 0.7 Mg 0.3 MoO 6−δ [167] and, after heat treatment at 1200 • C for 24 h, with Sr 2 CoMoO 6−δ [161], Sr 2 NiMoO 6−δ [161] and Sr 2 MgMoO 6−δ [168].…”
Section: Sample Samples Obtaining Method; Annealing Temperature (°C) ...mentioning
confidence: 88%
“…The chemical compatibility of La 1−x Sr x Ga 1−y Mg y O 3−δ was investigated with oxide materials used in SOFCs, cathodes [141][142][143][144][145][146][147][148][149][150][151][152] and anodes [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]: this is presented in the corresponding reviews [28,56,153].…”
Section: Sample Samples Obtaining Method; Annealing Temperature (°C) ...mentioning
confidence: 99%
“…As Sr 2 NiMoO 6-δ , Sr 2 MgMoO 6-δ can be obtained through different synthesis methods: solid state synthesis [ 19 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ], solution methods (including sol-gel technology using citric acid [ 24 , 37 , 45 , 72 , 104 , 105 , 106 , 107 ] and EDTA [ 20 , 76 , 77 , 108 , 109 ]), the combustion method using glycine as a fuel and complexing agent [ 110 , 111 ] and the freeze-drying method [ 88 , 108 ]. The main disadvantage of this compound is its non-single phase after synthesis in air ( Figure 8 ).…”
Section: Functional Properties Of Sr 2 Mmoo mentioning
confidence: 99%
“…The thermal compatibility of Sr 2 MgMoO 6-δ with an LSGM electrolyte was studied in [ 99 ]. It was found that an insignificant interaction between these components begins after annealing at 700 °C ( Figure 9 ).…”
Section: Functional Properties Of Sr 2 Mmoo mentioning
confidence: 99%
See 1 more Smart Citation